O auxílio direto no novo CPC - Gomes, Marcelo Sant'anna Vieira (2015)
Society is in evolution and with it the legal instruments follow the same tune. If previously the Code of Civil Procedure in force suited to historical reality 1973, today several of its devices do not already have conditions to settle their disputes with mastery. So, the New Civil Procedure Code comes with the intention to overcome major problems encountered, trim edges and clear any doubts. With a dedicated logic for cooperation between the parties and greater procedural effectiveness, the new law is enacted with the need to adapt the issues related to the process, the new reality that surrounds us. It is the first time that a national legislative instrument moves on to the right assistance and international legal cooperation instrument. That procedure was provided only in international treaties, as well as regulated by Higher resolution Court, by Resolution No. 09/2005, today to have their space in the new law. Therefore, this paper examines the claims of the legislature to regulate the direct aid and if this act brings some benefit to the concept of international legal cooperation. Makes an analysis in the light of the procedural, international and constitutional law, working with the hypothetical-deductive method. Should not be allowed to forget that with the enactment of the New CPC, Law 13,105, of March 16, 2015, it is necessary that the right operators and, in particular, procedural experts, to look into the new law in order to understand all your points, your paradigm shifts and the new procedure is conducted format in order to get work effectively, before those who need the public to settle their disputes. More than that. Whereas direct assistance can develop the administrative or judicial process, the researcher needs to understand how the operation, to turn, how to make a request for cooperation, as well as the requirements for their use. It is in this context that this work